Usage of Natural Colour Indicators in Packaging Materials for Monitorization of Meat Freshness - Pelin Talu Özkaya; Seval Dağbağlı (Turkish Journal of Agriculture: Food Science and Technology)
Food packaging has an important role in protecting food against physical, chemical, and biological hazards during storage and distribution and in informing the consumer about the product. The packaging of foods that susceptible to chemical / microbiological spoilage especially such as meat, hence limited storage time, is even more important than other foods. In addition, the tendency of health-conscious consumers to be a part of real-time controls and monitoring food safety has led to the widening of this packaging perception. Hence, there have been innovative studies in recent years, especially aiming real time monitorization of freshness indicators. The focus of these studies is “colour indicators” used in the production of intelligent indicator films and colorimetric sensors within specific matrices to be integrated into packaging materials. The colour indicators change colour in the presence of certain metabolites released in food spoilage, which allows freshness to be determined. Colour substances used for this purpose can be natural or synthetic. Hence, natural pigments such as anthocyanin, curcumin, etc. have been more preferrable since being harmless to the health as well as increasing tendency of consumers to utilization from natural resources. In this review, information about natural colour indicators and studies in which these indicators are used to determine the freshness of meat in real time and visually are given.